Monitoring nociception in patients with morbid obesity undergoing bariatric surgery - Salvatore Fabrizio Favitta; Danilo Santolamazza; Ersilia Luca; Roberto De Cicco; Paola Aceto (Saudi Journal of Anaesthesia, 2025)
Bariatric surgery is a rapidly developing field and presents a challenge for anesthesia management, especially in the treatment of acute postoperative pain. Severely obese patients have a greater risk of intra and postoperative complications due to their cardiovascular and respiratory pathophysiological alterations. Excessive fat also alters the normal metabolism of analgesic drugs, in particular opioids, thus reducing their therapeutic range and increasing the risk of reaching toxic doses with accumulation and overdose effects. Nociception, in contrast to pain, is not a subjective experience but a physiological response to a nociceptive stimulus, which manifests as objective modifications in vital parameters. An increasing number of monitoring methods have been approved in recent years, especially developed for the detection of intraoperative nociception to enable better control of opioid titration. This review aimed to provide an overview of the main monitoring systems commercially available devices, which could be used to monitor nociception during bariatric surgery. Eighteen studies evaluating the most widespread nociception monitoring systems were analyzed. These studies were mostly conducted on patients undergoing abdominal laparoscopic surgery, which is comparable to bariatric surgery in terms of pain stimulation. Intraoperative and postoperative opioid consumption were compared between patients subject to nociceptive monitoring and those in whom analgesia was guided by their changes in vital parameters. Although the devices seem able to optimize the anesthetic management of these patients, studies on bariatric populations are scarce and do not allow us to state whether the routine use of these tools can modify the patient’s clinical outcome.